Alternative solution for human error in hospitality industry - Ong Pearl Mares; Genta Bernard Mahardika; Muhammad Askha Rafliansyach Wijaya (Surya Hijau Manfaat, 2023)
A hotel is a service that offers accommodation to visitors. Things don't always go smoothly in the hospitality industry, so mistakes are bound to happen. Because guests feel uncomfortable or even make mistakes in cooperation between employees. Interpersonal problems are called human error. Human error or in another sense a standard deviation that can cause problems in the hotel. The cause of the problem itself stems from several factors that occur inside and outside the hotel. An example of a problem that arises in the hotel is the lack of knowledge and skills in dealing with guests. This requires solutions to improve employee performance through orientation and training provided by the hotel to educate employees even better. Usually the culprit of the problems that arise is the hotel staff, including managers, supervisors, insiders and others. Many different actions arise from the problem and all actions inevitably have a cause and effect, especially when it comes to the hospitality business. The purpose of the author writing this article is to know how to solve the problem with a good solution. The method used is qualitative, the author knows how to collect information from various sources. We, the author, tried to offer solutions and actions for human error in hotels.